Terrestrial cosmogenic nuclide bedrock depth profiles used to infer changes in Holocene glacier cover, Vintage Peak, southern Coast Mountains, British Columbia - A. C. Hawkins; B. M. Goehring; B. Menounos (Geochronology, 2025)
The majority of glaciers in North America reached their maximum Holocene downvalley positions during the Little Ice Age (1300–1850 CE), and in most cases, this expansion also destroyed earlier evidence of glacier activity. Substantial retreat in the 20th and early 21st centuries exposed bedrock that fronts many glaciers that may record Early to mid-Holocene exposure and later burial by ice, which can be elucidated using multiple-nuclide cosmogenic surface exposure dating. Cores of bedrock allow the measurement of cosmogenic nuclide depth profiles to better constrain potential exposure and burial histories. We collected four bedrock surface samples for 10 Be and 14 C surface exposure dating and shallow ( <0.6 m depth) bedrock cores from Vintage Peak, in the southern Coast Mountains of British Columbia, Canada. We apply a Monte Carlo approach to generate combinations of exposure and burial duration that can explain our data. We found that Vintage Peak became uncovered by the Cordilleran Ice Sheet between 14.5 and 9.7 ka, though upper elevations on Vintage Peak retained ice until 10–12 ka before retreating to smaller than modern positions. Glaciers on Vintage Peak advanced within 100 m of Late Holocene maximum positions around 4–6 ka. Poorly constrained subglacial erosion rates, possible inheritance, and variable mass shielding complicate our ability to more robustly interpret bedrock cosmogenic surface exposure histories. Nine 10 Be ages on Late Holocene moraines reveal that glaciers reached their greatest Holocene extents by ca. 1300 CE. Our results agree with other regional glacier records and demonstrate the utility of surface exposure dating applied to deglaciated bedrock as a technique to help construct a record of Holocene glacier activity where organic material associated with glacier expansion may be absent or poorly preserved. Further work to increase exposure and/or burial history modeling complexity may help to better constrain complex exposure histories in glaciated alpine areas.